Decomposing growth: Do low-income and HIPCs differ from high-income countries? ; growth, technological catch-up, technological change and human and physical capital deepening - Pertti Haaparanta; Heli Virta (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper studies the distribution of output per worker between the years 1980 and 2000 in different country groups. The study uses data envelopment analysis (DEA) to decompose the changes in the distribution of labour productivity into changes in productive efficiency, changes in best practice technology, accumulation of physical capital, and accumulation of human capital. The study focuses on low-income countries and within them on highly indebted poor countries (HIPCs), which has not been possible in earlier studies. – productivity ; efficiency ; developing countries
Keywords: O11; O47; O57; 330; Produktivität; Arbeitsproduktivität; Data-Envelopment-Analyse; Low-Income Countries; HIPC